2019
DOI: 10.4028/www.scientific.net/kem.816.202
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lubricants on Fiber Length Distribution and Properties of Glass Fiber Reinforced Composites Based on Polyamide 1010

Abstract: Influence of lubricants such as montan waxes and fatty acid esters, on properties of glass fiber reinforced composites based on polyamide 1010. Composites with 40 % wt. glass fibers were obtained on twin-screw extruder, while the fiber breakage occur. Fiber length distribution were measured. It is shown, that adding of 0.5 % wt. of lubricants increase content of glass fibers longer than 2 critical length and improve mechanical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…[ 49 ] The samples with GF were higher TMOE than those of wood fiber while it changed by reversal in the presence of AKD. [ 50 ] Investigated the lubricant effect on the mechanical properties of GF reinforced polymer composites. They concluded that the ester wax and fatty acid glycerol ester adversely affected MOE and other mechanical strengths of the GF plastic composite samples particularly when their amount was more than 0.5%wt.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 49 ] The samples with GF were higher TMOE than those of wood fiber while it changed by reversal in the presence of AKD. [ 50 ] Investigated the lubricant effect on the mechanical properties of GF reinforced polymer composites. They concluded that the ester wax and fatty acid glycerol ester adversely affected MOE and other mechanical strengths of the GF plastic composite samples particularly when their amount was more than 0.5%wt.…”
Section: Resultsmentioning
confidence: 99%
“…The lubricants such as waxy materials at high ratio diminished roughness on the surface by encapsulating GF, hence the adhesion of GF‐matrix interface declined. [ 45, 50 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, carbon fibers, in addition to the obvious reinforcement of the material, also provide better tribological properties by reducing the wear rate of the composite material. In contrast, glass fibers enhance the ability to absorb energy during dynamic impact, reducing the brittleness of the material [ 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, there is no research on this topic for PA 10.10. Cellulose [25,26], glass [27,28], basalt [29] and carbon fibers [30] are currently used to reinforce PA 10.10 to improve its properties.…”
Section: Introductionmentioning
confidence: 99%